STRATEGI PENYAMPAIAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI ANAK BERKEBUTUHAN KHUSUS DI SMA LUAR BIASA BHAKTI WANITA LUMAJANG - Imami, Vika NurYulia (Pendidikan Islam Pascasarjana IAIN Jember, 2018)
Abstract Education is a place for individual to improve Intelektual Question (IQ), Emotional Question (EQ), Spiritual Question (SQ), also skill or competency in personal ourselves. But not all the children were born normally and perfect. We can see there are many children have disabilities phisically and mentaly. Disability children (ABK) is an idiom for children who have disability. Disability Senior High School (SMALB) Bhakti Wanita Lumajang is a special department which is holding education for disabililty children for all kind of disabilities, such as child with impaired vision or tunanetra (A), hearing disorders and talking or tunarungu wicara (B), child with mental disorder or tunagrahita (C), and disability or tuna daksa (D). The curriculum purpose at Disability Senior High School (SMALB) Bhakti Wanita Lumajang is not communities necessities, but how with their capability and skill in them they can be accepted by the communitiy. Strategy of delivering learning that is used in learning process has an important role and take precedence, so that what has planned and concepted before by a educatior especially indicator achievement of learning deals with the purpose that has been decided.